Complete mitochondrial genome of the radicine pond snail Radix plicatula (Gastropoda: Lymnaeidae). Issue 2 (3rd July 2019) - Qin, Dong-Mei; Huang, Xiao-Chen; Yang, Li-Min; Liu, Xiong-Jun; Wu, Rui-Wen; Ouyang, Shan; Wu, Xiao-Ping; Wang, Shang-Hong
Abstract: Radix plicatula is broadly distributed in China, as well as Russia. It is one of the intermediate hosts of Fasciola species which leads to the spread of fascioliasis. Here, we first described the complete mitochondrial genome of R. plicatula . The mitogenome is 13, 751 bp in length, containing 13 protein-coding genes, 22 tRNA genes, and 2 rRNA genes. The contents of each base are 30.7% A, 39.6% T, 15.7% G, and 13.9% C. The sequence is AT rich (70.3%). Mitochondrial phylogenomic analysis showed that R. plicatula is close to R. auricularia .